2015
DOI: 10.1503/cjs.002315
|View full text |Cite
|
Sign up to set email alerts
|

The importance of tailoring physicians’ trauma care training needs in rural environments

Abstract: 425areas. The ATLS, PALS and other trauma educational offerings should be more accessible, and greater use of tele-education should be considered. Furthermore, courses focusing on trauma team approaches in the context of scarce resources (e.g., RTTDC) need greater promotion and emphasis. We believe that educational opportunities will be more effective if learning is based on real cases from the local setting, and real-time consultation will provide physicians the training and support they require to in turn pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…Providers in this study reported how fatigue impacts documentation, directly affecting development and implementation of a TR. Training levels and experience of providers are known to impact care of injured patients [ 41 , 42 ]; existing literature aligns with that we found - that providers perceived junior doctors as being unreliable to perform proper documentation linked to the care provided. Some participants highlighted that the provision of care was not matching documentation; consequently, the patient would receive more care and less documentation, especially if the attending provider is senior.…”
Section: Discussionsupporting
confidence: 80%
“…Providers in this study reported how fatigue impacts documentation, directly affecting development and implementation of a TR. Training levels and experience of providers are known to impact care of injured patients [ 41 , 42 ]; existing literature aligns with that we found - that providers perceived junior doctors as being unreliable to perform proper documentation linked to the care provided. Some participants highlighted that the provision of care was not matching documentation; consequently, the patient would receive more care and less documentation, especially if the attending provider is senior.…”
Section: Discussionsupporting
confidence: 80%
“…Many rural EDs are staffed by physicians not board‐certified in emergency medicine or by advanced practice providers (e.g., physician assistants or nurse practitioners) with no real‐time on‐site physician supervision . Despite the increased prevalence of traumatic injury and trauma‐associated death in rural populations, severe trauma remains an infrequently treated condition in many low‐volume EDs, and many rural providers may be less comfortable with trauma management and care …”
Section: Discussionmentioning
confidence: 99%
“…24 Despite the increased prevalence of traumatic injury and trauma-associated death in rural populations, 2,3 severe trauma remains an infrequently treated condition in many low-volume EDs, and many rural providers may be less comfortable with trauma management and care. 25 Another reason for consultation for these patients is the significant administrative function that the telemedicine hub serves. In the telemedicine network, hub staff provide real-time nursing documentation for rural critically ill patients, enter orders in the rural hospital medical record, and arrange transfer by contacting receiving hospitals and emergency medical services agencies.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, rural physicians have expressed interest in managing patients with pediatric, orthopedic, vascular and blunt thoracic or abdominal trauma. 25 Although courses such as ATLS and the Rural Trauma Team Development Course (RTTDC) may bridge these knowledge gaps, it may not be realistic or feasible to take health care providers away from the sparsely served rural sites they service to provide training. Our study did not examine differences in hospitals that have RTTDC personnel at any point during or before the study period.…”
Section: Discussionmentioning
confidence: 99%